1979
DOI: 10.1172/jci109523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Colchicine in Acute Urate Crystal-Induced Arthritis

Abstract: A B S T R A C T Phagocytosis of urate crystals by human or rabbit neutrophils induces the synthesis and release of a glycoprotein, the crystal-induced chemotactic factor (CCF), which is chemotactically active both in vitro and in vivo. It has been proposed that CCF is a prime mediator of the acute gouty attack. Colchicine has been shown to decrease the production and release of this factor in vitro. In these studies, colchicine, at nonleukopenic doses, is shown to abrogate the acute arthritis induced by monoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 19 publications
1
18
1
1
Order By: Relevance
“…This could imply a preference of the rabbits for MeS, supposing that their stems and leaves were easier to grab. Spilberg et al (1979) reported the first adverse effects when animals were exposed to 0.2 mg/kg BW of colchicine, which is less than the exposure of 0.8 and 1.2 mg/kg BW in the maximal level group in our study. The question about whether the appearance of MeS refusals in the maximal dose group (on av.…”
Section: Effects Of Mes Presencecontrasting
confidence: 60%
See 2 more Smart Citations
“…This could imply a preference of the rabbits for MeS, supposing that their stems and leaves were easier to grab. Spilberg et al (1979) reported the first adverse effects when animals were exposed to 0.2 mg/kg BW of colchicine, which is less than the exposure of 0.8 and 1.2 mg/kg BW in the maximal level group in our study. The question about whether the appearance of MeS refusals in the maximal dose group (on av.…”
Section: Effects Of Mes Presencecontrasting
confidence: 60%
“…However, impact of the colour on consumption was not tested in this study, because we chose to treat colour as a factor in the buying decisions of pet owners. Therefore, even if owners (commercial breeders as well as pet owners) were shown to buy hay of an intense green colour rather than a yellow hay (Stainmesse 2015), it should have no impact on the sale of the tested hays.…”
Section: Hay Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, hFpB contrasts with C5a, fMLP, or LTB4 and resembles instead a factor generated from plasma by superoxide (48) and the synthetic tripeptide, gly-his-gly (49), which also causes PMN chemotaxis without causing PMN secretory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Isaías Spilberg a fines de los 70 e inicios de los 80, se dedicó a investigar el rol quimiotáctico que ejercen los cristales de urato monosódico sobre el leucocito y la interrupción del mismo con colchicina (3,4).…”
Section: Hiperuricemia Y Alturaunclassified